2020
DOI: 10.1038/s41467-020-17321-2
|View full text |Cite
|
Sign up to set email alerts
|

Structurally divergent dynamic combinatorial chemistry on racemic mixtures

Abstract: Structurally Divergent Reactions on Racemic Mixtures are atypical processes in Nature. The few examples reported in the literature take place in organic solvents and are driven by the reagents' interaction with bulky chiral catalysts. Herein, we describe a dynamic combinatorial approach to generate structural divergence from racemic building blocks. The divergence is due to a stereospecific electron-donorelectron-acceptor interaction of diastereomeric macrocycles, leading to structurally distinct pseudorotaxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…of the building blocks, while efficient covalent bond formations such as click reactions, 30 alkene metathesis 31 and dynamic covalent bond forming reactions ( e.g. imine 32 and disulfide 33 ) can give MIMs in high yields.…”
Section: Catenane Synthesismentioning
confidence: 99%
“…of the building blocks, while efficient covalent bond formations such as click reactions, 30 alkene metathesis 31 and dynamic covalent bond forming reactions ( e.g. imine 32 and disulfide 33 ) can give MIMs in high yields.…”
Section: Catenane Synthesismentioning
confidence: 99%
“…Pantos et al. described the stereodivergent formation of diasteroisomeric catenanes which is dramatically governed by the configuration of the cysteine pending groups [51] . While both studies involve chiral building blocks, the only example involving an achiral building block was provided by Otto et al.…”
Section: Synthesis‐structure‐function Relationshipsmentioning
confidence: 99%
“…[50] Pantos et al described the stereodivergent formation of diasteroisomeric catenanes which is dramatically governed by the configuration of the cysteine pending groups. [51] While both studies involve chiral building blocks, the only example involving an achiral building block was provided by Otto et al who reported that casting or molding could switch the selectivity of the assembling event toward the preferential formation of one configurational stereoisomer vs another. [52] The authors could come to this conclusion by determining whether head-to-head or headto-tail fragments were generated upon MS/MS fragmentation of library members within the libraries.…”
Section: The Stereochemical Landscapementioning
confidence: 99%
“…In both cases, a posteriori analyses indicate that the stereoreselectivity of the assembling process is guided by steric interactions which propagates (figure 1b, blue arrow and highlight) either during chain growth (cucurbiturils) or ring closure (pillararenes) 36 . In the field of disulfide based cavitands, which can be assembled by dynamic combinatorial strategies, examples of stereoselective assembling remain scarce and almost systematically involve chiral building blocks [37][38][39][40] . Template-induced (by casting and/or molding) selection and amplification of different facial stereoisomers of polydisulfide cyclotetramers was reported by Otto et al 38,41 Yet, the rationale enabling to program on demand the configuration and conformation of a macrocycle by exploiting the stereochemical features of its building blocks and of the template used has remained out of reached so far.…”
Section: Introduction the Concept Of Molecularmentioning
confidence: 99%